Dakwah dengan Metode Intervensi Kognitif dalam Improving Persepsi Keagamaan Napi Teroris di Lapas Garut - Hajir Tajiri (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
This study aims to reveal the religious perceptions of terrorist convicts in Garut Prison, the use of cognitive interventions in improving religious perceptions and the success of using cognitive intervention techniques in improving religious perceptions. The research used a qualitative approach with descriptive methods and data collection through observation and interviews involving interventors with national, religious, and terrorist insights in Garut penitentiary. The results show that the religious perceptions of terrorist convicts deny the foundations of the Republic of Indonesia as contrary to Shari'a, dissatisfied with Pancasila and the 1945 Constitution because they are considered inconsistent with their beliefs. The BNPT team returned the prisoners' perceptions by using cognitive interventions, namely providing new and strengthening views about the basis of the state which were explored and formulated by the founding fathers, leaders and Islamic scholars. This technique is able to change the religious perception of terrorist convicts as shown by the readiness of terrorist convicts to return to the Republic of Indonesia, accept Pancasila, the 1945 Constitution and are ready to live life as good citizens. The implication is that cognitive intervention can be categorized into the da'wah method, namely mujilah ahsan.